Opportunities of diagnostic imaging in monitoring the radiosurgery treatment for uveal melanoma (Ukrainian Journal of Ophthalmology, 2025)
Background: Uveal melanoma (UM) is a primary choroidal tumor of neuroectodermal origin with a high malignant potential. Organ-preserving stereotactic radiosurgery (SRS) treatment strategies can be used for patients with UM.Purpose: To assess the potential of diagnostic imaging methods, computed tomography (CT) and magnetic resonance imaging (MRI), for the monitoring of SRS treatment outcomes for UM.Methods: Twenty-six patients with UM (age, 27 years to 68 years) were involved in this study and underwent an examination. The uveal melanomas were classified as per the classification system by Shields. A standard bolus protocol with iodine-containing contrast agent (Ultravist) was used to perform CT imaging on an Activion TSX-031A Multislice CT Scanner. A standard brain MRI protocol (Т1, Т2, FLAIR, T1 Fsat, T2 Fsat, Short 3D 2mm T1) with non-ionic paramagnetic contrast medium (Omniscan™) was used to perform diffusion-weighted MRI and obtain apparent diffusion coefficient (ADC) values on a 1.5T Vantage Atlas MRI system. The G4 Cyberknife System was used to perform SRS treatment for UM with the clinical target volume coverage of 99.9%. Results: Post-SRS changes in semiological elements in CT and MRI images were examined. Our imaging monitoring of patients with UM showed that UM ADC values substantially increased as early as month 1 or month 2 after SRS (whereas tumor tissue volumes decreased only 6 months after SRS). Thus, in small, medium-size and large tumors, UM ADC values increased by 18.1%, 20.0%,  and 35.7 %, respectively, at 1-2 months, and by  41.9%, 38.8%, and 64.3%, respectively, at 11-12 months.Conclusion: CT and MRI are diagnostic imaging modalities provide valuable information in monitoring patients with UM. Diffusion-weighted MRI provides qualitative and quantitative characteristics of post-SRS changes in tumor process.
Keywords: uveal melanoma; CT; MRI; stereotactic radiosurgery